Pembuatan Abon Ayam Berbagai Rasa Sebagai Alternatif Lauk Pengganti - Marhayati; Putra, Reski Praja; Setialaksana, Wirawan; Wahid, Abdi; Rasjid, Ramli (Jurusan Pendidikan Teknik Elektro, 2025)
Training activities on making various flavors of chicken floss were carried out as an effort to improve the community's skills in producing practical, nutritious, and long-lasting ready-to-eat side dishes. The objectives of the training were to provide technical knowledge on making chicken floss in various flavors, train participants to produce chicken floss that is safe for consumption and has a long shelf life, encourage the creation of micro-business opportunities based on local food processing, and strengthen household food security through the diversification of ready-to-eat side dishes. Chicken floss was chosen as the training material because of the easy availability of raw materials, a relatively simple production process, and the opportunity to develop a variety of flavors that can be accepted by various consumer groups. The training covers the stages of raw material selection, hygienic processing techniques, spice formulation for various flavors (original, spicy, sweet-spicy, and herbal), drying techniques, packaging, and food safety standards. This activity involves target community groups, particularly housewives and local MSME actors, using demonstration, hands-on practice, and mentoring methods. The results of this activity show an increase in participants' ability to understand safe, consistent production techniques that meet household and small business standards. In addition, participants are able to produce chicken floss in several flavors that are suitable for consumption and have the potential to be developed as an alternative side dish in everyday life. Another impact is the increased motivation of the community to develop food processing businesses and the creation of new economic opportunities based on local product innovation. Thus, this training contributes to improving family food security and strengthening the local community's economy.